Optimal dynamic pricing under network externalities - Seiya Hirano (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This paper studies the relationship between optimal dynamic pricing for network goods and the coordination of consumers' adoption decisions. We show that based on risk dominance criterion, consumers face the risk of coordination failure, and introductory pricing is optimal if the risk is higher in period 1 without network. We find that under threshold coordination, the impact of price on the network size varies according to consumer beliefs. In pessimistic (optimistic) threshold coordination, the network size expands (shrinks) as the price increases. Lowering (Raising) the price in period 2 implies a smaller network size, so introductory (skim) pricing is optimal.
Keywords: 330; Network Externalities; Dynamic Pricing; Coordination Game